A 2018 Social Accounting Matrix for Germany depicting waste and recycling accounts for a circular economy - Gero Elshof; Jonas Jens Luckmann; Khalid Siddig (Humboldt-Universität zu Berlin, Faculty of Life Sciences, Department of Agricultural Economics, 2022)
The 2018 SAM for Germany comprises of 160 accounts including 63 activities, 85 commodities, margins, labor, capital, household, government, social contributions, taxes on products, activity tax, direct tax, stock change, savings and investment and the rest of the world. It is entirely based on data from the Federal Statistical Office of Germany (Destatis), which guarantees the highest possible degree of data-consistency. Because the initial version of the SAM (Proto-SAM) has imbalances in the government, savings and investment and the rest of the world accounts, a balanced SAM is estimated using the cross-entropy method. To ensure the consistency of the data through the estimation process, macro totals are enforced as controls for total imports, total value-added, total private consumption, total government consumption and total exports.
Keywords: E16; Q53; 330; social accounting matrix; Germany; circular economy; recycling